Climatic caracterization of the atmospheric circulation in south america - Saavedra, Miguel (2011)
In the present paper, using the data obtained by Reanalysis we identify the main patterns of atmospheric circulation in South America. For the processing of information, we made not distinction between El Niño, and No El Niño years, considering only averages of the main meteorological variables for the patterns identification. By analyzing the graphs of atmospheric pressure and winds, it was identified that the surface circulation is governed mainly by the presence of anticyclones in the Pacific and South Atlantic, and high levels of the system called Alta Bolivia, whose influence is seen from 500 hPa. On the other hand, the rainfall patterns highlight the Intertropical Convergence Zone, ITCZ, the Convergence Zone of the South Atlantic, SACZ, and the coastal deserts are located along the coasts of Peru and Chile. The ITCZ oscillates near the Equator, with maximum values of precipitation and zonal winds, resulting from the converge of the wind systems of the northern and southern hemispheres.